Electromechanical factors associated with response to cardiac resynchronization therapy. (3rd October 2022) - Jadczyk, T; Maffessanti, F; Wilczek, J; Conte, G; Caputo, M L; Golba, K S; Biernat, J; Cybulska, M; Caluori, G; Regoli, F; Krause, R; Wojakowski, W; et al.
Abstract: Background: Cardiac resynchronization therapy (CRT) is clinically proven in patients with heart failure (HF) and left bundle branch block (LBBB). However, approximately 30% of CRT individuals are non responsive to the therapy while factors affecting electromechanical coupling remain not fully understood. Objective: To determine the optimal combination of electromechanical parameters associated with responsiveness to CRT. Methods: Sixty-two patients with HF/LBBB underwent invasive anatomo-electromechanical mapping (AEMM) of the left ventricle using NOGA XP system (Biosense Webster), cardiac magnetic resonance (cMR), transthoracic echocardiography and 12-lead ECG. Remodeling was quantified based on the end-systolic volume (ΔESV) decrease at 6-month follow-up. Response to CRT was defined as ΔESV ≤−15%. QRS duration (QRSd) was measured from a surface ECG. Area strain was obtained from AEMM and used to calculate systolic stretch index (SSI) and total left ventricular mechanical time (TLVMT). Total left ventricular activation time (TLVAT) and transeptal time (TST) were derived from AEMM and ECG. Scar burden was evaluated from cMR late gadolinium enhancement imaging. Results: Significant correlations were observed between ΔESV and TST (rho=0.42; responder: 50 [20–58] vs non-responder: 33 [8–44] ms), TLVAT (−0.68; 81 [73–97] vs 112 [96–127] ms), scar burden (−0.27; 0.0 [0.0–1.2] vs 8.7 [0.0 19.1]%) and SSI (0.41; 10.7 [7.1–16.8] vs 4.2 [2.9–5.5]), but not QRSd (0.11; 155 [140–176] vs 167 [155–177] ms). TLVAT and SSI had a high predictive value for CRT response (AUC>0.80). TLVAT (OR=1.50), scar burden (0.91) and SSI (0.04) were independent factors associated with a positive response to CRT. Individuals with SSI >7.9% and TLVAT <91 ms all responded to CRT, while low SSI and prolonged TLVAT were more common in non-responders. Conclusion: Electromechanical parameters show better correlation with CRT response than traditional surface ECG measurements. The absence of scar combined with high SSI and low TLVAT ensures effectiveness of CRT. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Swiss National Science Foundation, Statutory funds of the Medical University of Silesia